MENGENAL ERGONOMI KERJA YANG BAIK SAAT BERAKTIVITAS DI KANTOR - Adi Saputra Junaidi; Attika Ayu Putri Mayang Sari (Jurnal Abdimas Kesehatan (JAK), 2019)
Ergonomics is one of the functions in increasing productivity in the form of rules in work that intends to make the working safe system, healthy, safe and comfortable. The incompatibility of ergonomic factors will result in errors in the work posture and generally accompanied by musculoskeletal symptoms in the form of pain. Ergonomics of work posisition in work is very important, if the work posisition is contrary to the body's natural will cause fatigue and injury to the muscles. The method or implementation of community service is in the form of percentage of power points, leaflets, banners, and education and simulation. The conclusion is an understanding of the importance of ergonomic positions when working along with stretching actions or movements that must be done at rest and the ideal resting time when working or doing activitie